2020
DOI: 10.1186/s12886-020-01497-8
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk of tinnitus in patients with early-onset cataracts: a nationwide population-based case-control study

Abstract: Background: This study aimed to investigate the association between early-onset cataract and tinnitus using a population-based database. Methods: Retrospective claims data from the Taiwan National Health Insurance Research Database were analysed. Study subjects comprised patients with early-onset cataract, aged 20-55 years and diagnosed between 2000 and 2010 (n = 2084) and a comparison cohort without the disease (n = 8336). Both cohorts were followed until 2010 to estimate the incidence of tinnitus. To calcula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…In addition, the number of individuals with comorbidities (anxiety, hearing loss, vertigo, insomnia) was significantly higher among the patients with cataract than in controls [445]. Furthermore, other studies showed that hearing loss, insomnia and anxiety were highly relevant to tinnitus severity [445][446][447][448]. Interestingly, Neri et al [449] showed that the levels of oxidative damage markers (malondialdehyde, myeloperoxidase, 4-hydroxynonenal) were significantly higher in patients with tinnitus than in controls, whereas glutathione peroxidase (an antioxidant) had lower activity, thus probably sharing similar pathogenesis with development of cataract.…”
Section: Hearing Loss Tinnitus Vibrations Whiplash Trauma and T Gondi...mentioning
confidence: 88%
See 1 more Smart Citation
“…In addition, the number of individuals with comorbidities (anxiety, hearing loss, vertigo, insomnia) was significantly higher among the patients with cataract than in controls [445]. Furthermore, other studies showed that hearing loss, insomnia and anxiety were highly relevant to tinnitus severity [445][446][447][448]. Interestingly, Neri et al [449] showed that the levels of oxidative damage markers (malondialdehyde, myeloperoxidase, 4-hydroxynonenal) were significantly higher in patients with tinnitus than in controls, whereas glutathione peroxidase (an antioxidant) had lower activity, thus probably sharing similar pathogenesis with development of cataract.…”
Section: Hearing Loss Tinnitus Vibrations Whiplash Trauma and T Gondi...mentioning
confidence: 88%
“…Tinnitus and cataracts also were reported to have a significant relationship with the parasite infection [443,444], and Hsieh et al [445] found that patients with cataract had higher hazard ratio developing tinnitus than controls (OR = 1.53, 95% CI: 1.17-2.01, p < 0.01). In addition, the number of individuals with comorbidities (anxiety, hearing loss, vertigo, insomnia) was significantly higher among the patients with cataract than in controls [445]. Furthermore, other studies showed that hearing loss, insomnia and anxiety were highly relevant to tinnitus severity [445][446][447][448].…”
Section: Hearing Loss Tinnitus Vibrations Whiplash Trauma and T Gondi...mentioning
confidence: 99%
“…Intriguingly, not only the somatosensory system may be involved in tinnitus. Visual snow, the visual analogue of tinnitus [ 29 ], is comorbid with tinnitus [ 30 ], and cataract is a risk factor for tinnitus [ 31 ]. This suggests that possibly not only the somatosensory system is involved in tinnitus generation but in some patients the visual system may influence it.…”
Section: Etiological Factorsmentioning
confidence: 99%
“…Presenile cataract is defined as the opacification of lens and/or its capsule before the age of 50 years when all other known causes of cataract have been ruled out [8][9][10] . This will definitely add on to the already existing burden of age-related cataract in India and worldwide.…”
Section: Introductionmentioning
confidence: 99%